Assessment of the effectiveness and efficiency of packaging waste EPR schemes in Europe. (1st July 2022) - Colelli, Francesco Pietro; Croci, Edoardo; Bruno Pontoni, Federico; Floriana Zanini, Sara
Highlights: We study the performance of packaging EPR in the EU with novel industrial data. PROs achieving higher recycling rates do not entail necessarily higher costs. Non-competitive systems are more successful in increasing recycling rates. Systems that exclude local authorities in the collection underperform. Abstract: This paper provides an analysis of the performance of European packaging waste systems, focusing on Extended Producer Responsibility schemes and Producer Responsibility Organizations. We adopt two separate but complementary empirical analysis: i) an indicator-based assessment of the cost-efficiency and recycling effectiveness of PROs; ii) a regression analysis of the determinants of recycling rates at the national level. The analysis spans over 25 national schemes and 21 Producer Responsibility Organizations. Our findings show that systems that have higher recycling rates do not entail necessarily higher costs. Non-competitive systems are more successful in increasing recycling rates no matter the cost; moreover, they are better able to use funds collected from EPR fees charged to producers, delivering improved cost-efficiency. Furthermore, higher recycling rates are associated with systems in which local authorities retain the operational responsibility of collection. Systems that do not involve local authorities always underperform. The policy implications are clear: local authorities should have some responsibility for collecting and sorting packaging waste and competitive systems should not be looked at as a first choice when designing a national recycling strategy. A mix of policy schemes, including non-profit EPR, door-to-door collection and Deposit-Refund-Schemes can be effective strategies for increasing the recycling rates of the waste streams that need more intervention, most notably plastic packaging.